Mô hình hóa 3D ảnh cộng hưởng từ chức năng sử dụng công nghệ Augmented reality (thực tế tăng cường) /Nguyễn Huy Anh. - Nguyễn, Huy Anh.
Augmented Reality is the hot trends developing techniques nowadays. Developer around the world day by day is keeping research and make them more and more familiar in people's life. Especially, that technique finding itself very useful in bio-medical generally and surgery privately. In this paper, i present my approach of AR technique to pre-surgery on PC.